Pineal cyst surveillance in adults – a review of 10 years' experience. (2nd September 2020) - Storey, Mathew; Lilimpakis, Konstantinos; Grandal, Nora Sangvik; Rajaraman, Chittoor; Achawal, Shailendra; Hussain, Masood
Abstract: Objective: Pineal cysts are common benign incidental findings in adults. There are no commonly accepted criteria for follow up or indications for intervention. We looked at our outcomes for this condition to explore their natural history and review our surveillance criteria. Method: Retrospective review of multidisciplinary team meetings at a tertiary neurosurgical centre over 10 years. Data relating to demographics, presenting symptoms, maximum diameter, duration of surveillance, final diagnosis and overall outcome were extracted from electronic patient records and available MRI. Data were analysed using IBM SPSS version 24. Result: Seventy-seven pineal cysts were identified. Female to male ratio was 1.43, female mean age was 38.6 and male mean age was 50.4. An increase in referral frequency was observed over the study period (mean increase of 1.4 cases per year). Presenting symptoms of headache in 45% and visual and hearing symptoms in 38.5% were recorded and baseline mean maximum diameter was 13.4mm. 20 patients were discharged on presentation, 54 were booked for at least one follow-up scan with a median follow up period of 14 months. The mean change in maximum diameter was 0.04mm over 18 months. Three patients (3.9%) underwent endoscopic biopsy and CSF diversion for cysts all more than 20mm with radiological evidence of hydrocephalus. In 100% of cases, the initial MDT diagnosis and final diagnosis were concordant. Conclusions: No patient under surveillance required surgical treatment and those managed surgically were symptomatic with large cysts and hydrocephalus on presentation. A majority of pineal cysts remained unchanged during the MRI follow-up, therefore our review suggests that routine follow-up of pineal cysts is not necessary in the absence of unusual radiological characteristics or related clinical symptoms.